La Garantía del Derecho a Probar y la Actuación Oral de la Prueba Documental en el Nuevo Proceso Laboral - Rayco Castañeda, Fanny Janeth (2017)
The two central aspects of the investigation are the analysis of the evidence provided to the labor process and the content of the right to the test that must be guaranteed in all actions of the test; determining in this sense that documentary evidence in the labor process to be particular in its scope qualifies complex, so that to be brought to the attention of the judge is postulated as a tool to the systematization of said test in order to enable its performance, the same that according to the values on which the New Labor Procedural Law (Law 29497) is based and the requirement also contained in this rule for the judge to immediately rule the culmination of the trial hearing with the final allegations must be oral so that in said act the judge makes direct contact with the information contained in the evidence, and therefore can resolve the case at the opportunity established by law as a general rule. Form of action that according to the doctrine and procedural rule is essential for the judge to acquire conviction of the facts in the same hearing of judgment, reason why it can legitimately be demanded its use to the party in the performance of the complex documentary evidence for the purposes of its assessment. Although the results of its application in Trujillo labor courts, according to the analysis of the sample (file processed during the years 2015 and 2016) to which the investigation has been directed, is, to say the least, due to the absence systematization of the test and its timely presentation that would facilitate its oral performance, even supporting the judges this disuse of this requirement that reinforces the exercise of the right to the test with the assessment of the test regardless of its performance in the form in view of the new scheme for the resolution of labor disputes which guarantees - if practiced - not only the effectiveness of the trial hearing but also seeks to make the right to trial tangible.